Law Enforcement Against Digital Businesses (E-Commerce) by The Business Competition Supervisory Commission (KPPU) in Competition Practices Unhealthy Business - Manan, Abdul; Nafri, Moh.; Permana, Mohamad Didi (Sinergi International Journal of Law, 2025)
The aim of the research is to find out and analyze the role of the Business Competition Commission (KPPU) in digital business and to know and analyze law enforcement by the KPPU regarding digital-based business activities. The research method uses normative legal research which uses primary legal materials and secondary legal materials which are then presented in the form of an inductive thinking pattern, namely from specific things to general things. The research results found that the Business Competition Commission (KPPU) in Indonesia has a very important role in maintaining healthy competition in the market, including in the context of rapidly developing digital business. The KPPU is tasked with monitoring and taking action against business practices that can harm healthy competition. In digital business, this includes monitoring large companies that have the potential to dominate the market, such as e-commerce platforms, social media or other digital services. Law enforcement against unfair business competition practices in digital business, especially e-commerce, is becoming increasingly relevant as the industry develops. In this context, the Business Competition Supervisory Commission (KPPU) has an important role in maintaining healthy competition and ensuring that all business actors in the e-commerce sector operate in accordance with applicable legal provisions. The research suggestion is that effective law enforcement against unfair business competition practices in digital business by the KPPU requires a more innovative and responsive approach to digital dynamics. Strict supervision, international collaboration, and the use of technology will increase the KPPU's effectiveness in keeping Indonesia's digital market fair and competitive.